The Role of the Sharia Supervisory Board on Muamalah Principles Compliance in Islamic Financial Institutions - Az Zahra, Faiza; Khoirunnisa, Nabila (Journal of Islamic Contemporary Accounting and Business, 2025)
This study discusses the role of the Shariah Supervisory Board in ensuring Islamic financial institutions’ compliance with Islamic law principles. The Shariah Supervisory Board plays a crucial role in overseeing and issuing fatwas regarding the permissibility of financial products and services offered by these institutions. The research also identifies challenges faced by the Shariah Supervisory Board, such as differences in the interpretation of Islamic law, technological advancements, and global competitive pressures. Additionally, the paper offers recommendations for strategies to strengthen the Shariah Supervisory Board’s role in maintaining Shariah compliance. In conclusion, the study emphasizes the Shariah Supervisory Board’s importance in guaranteeing the integrity and sustainability of Islamic financial institutions amidst increasingly complex challenges.